Pengelolaan Kolaboratif Kawasan Konservasi Penyu Pangumbahan Kabupaten Sukabumi - Irma Minarti Harahap; Achmad Fahrudin; Yusli Wardiatno (Institut Pertanian Bogor, 2015)
Establishment of Marine Protected Area Sukabumi once the backup area Pangumbahan as Turtle Beach Coastal Conservation Areas and Small Islands (KKP3K), directly or indirectly, in desperate need of local community participation in the management of the region. Public perception of environmental conservation activities in the region is expected to help better management activities in the marine conservation area. The results of the analysis of the validity and reliability of the indicator variables assessed showed that each variable has a value Corrected Item-Total Correlation greater than 0.300. While the reliability value is greater than 0.700, i.e. 0.827 (perception), 0.897 (participation), 0.894 (law enforcement), 0.858 (policy), and 0.846 for the variable management. Based on the analysis of variables concluded that the perception of stakeholders and local government policies related Pangumbahan Turtle Conservation Area is the most dominant variable in determining the success of the conservation area management.